79 DIABETES AND YOUNGER AGE PREDICT SUBOPTIMAL PLATELET INHIBTION IN PATIENTS RECEIVING ADJUNCTIVE TIROFIBAN AND ENOXAPARIN. (1st March 2005) - Nathan, S.; Kumar, A.; Chan, R.; Senter, S.; Almeda, F.
Abstract : Background: Platelet inhibition with tirofiban is variable but it remains unclear which patients (pts) manifest reduced antiplatelet response. We sought to identify factors predictive of suboptimal platelet inhibition in pts receiving tirofiban and enoxaparin. Methods: 60 consecutive pts received IV enoxaparin (0.75 mg/kg) and tirofiban (10 mg/kg bolus + 0.15 μg/kg/min infusion) at the time of elective PCI. Platelet aggregation was serially measured using a light absorbance platelet assay. Pts were divided by optimal (≥95%, n = 45, Group 1) vs suboptimal (< 95%, n = 9, Group 2) platelet inhibition at PCI and compared with regard to clinical variables. Results: Mean procedural platelet inhibition was<95% in 17% of pts. Groups were similar with regard to sex, HTN, smoking, lipids, wt, GFR, baseline platelet count and aggregation. Inhibition differed significantly between Groups 1 and 2 (Figure ) at PCI and continued to diverge. By multivariate analysis, diabetes and younger age were associated with suboptimal platelet inhibition: DM [RR = 8.14 (95% CI 1.43-46.33) p = 0. 018], younger age (per year) [RR = 0.89 (0.81-0.98) p = 0.018]. Conclusions: A minority of pts receiving tirofiban/enoxaparin evidenced suboptimal procedural platelet inhibition with continued divergence seen from those initially optimally inhibited. Diabetes and younger age were associated with suboptimal platelet inhibition. Surveillance of platelet inhibition and adjusted dosing regimens of tirofiban may be warranted in these pts.